Edukasi Strategi Pendampingan Belajar dari Rumah untuk Membangun Situasi Belajar Kondusif di Lingkungan Candi Baru, Gianyar - Sukaningsih, Ayu; Kadek Devi Kalfika Anggria Wardani; A.A. Ngr. Eddy Suriyadinata Gorda (Politeknik Negeri Madiun, 2022)
Since December 2019, the world has been shocked by the Covid-19 virus which can be transmitted through small droplets that come out when sneezing from the nose or mouth of people who are infected with the virus. To break the chain of spreading this virus, the government enforces a rule that all activities are carried out from home, including learning activities. Through community service activities carried out by this author, it aims to determine the effectiveness of online learning mentoring education for parents whose children are following the online learning process from home, so as to reduce the difficulties of parents when accompanying their children to learn from home. The target partners of this service are several communities whose children study online at home in the Candi Baru neighborhood, Gianyar. The method used in this study is the PAR research method, which is a method that emphasizes the participation and collaboration of various parties in managing a research. This research shows that the provision of online learning mentoring education can increase parents' knowledge and understanding of online learning.